Enhancing milk yield and quality of holstein friesian through special formulation urea molasses multinutrient block - A. Arif Rahma; Renny Fatmyah Utamy; Ambo Ako; Mohammad Mijanur Rahman; Siti Annisa Sukri (ResearchersLinks Ltd, England, UK., 2025)
The production of urea molasses multinutrient block (UMMB) typically involves cement and molasses. However, prolonged use of cement can lead to health issues in livestock, while molasses is often in short supply due to its extensive use as a raw material in various industries. Thus, alternative materials are highly needed as substitutes for both cement and molasses. This study assesses the effects of using cocoa pulp as filler and tapioca meal as an adhesive in UMMB production on Holstein Friesian dairy cows’ performance, milk yield, and milk quality. The experiment applied a complete randomized design (CRD) with three treatments, namely without UMMB supplementation (T0 as control), supplementation with 500g of regular UMMB (T1), and supplementation with 500g of UMMB made with cocoa pulp and tapioca meal (T2). Each treatment had five replications. The results indicated that UMMB supplementation significantly affected (p < 0.05) forage dry matter intake (DMI), total DMI, milk fat, and milk viscosity. Up to 50% of the molasses and cement used in UMMB production can be replaced with cocoa pulp and tapioca meal without reducing the final product’s physical quality. Substitution of molasses filler and cement adhesive with cocoa pulp and tapioca meal enhances forage DMI and total DMI while maintaining the yield and physical quality of milk in Holstein Friesian cows.